Greenhouse gas concentrations and emissions from a plastic-lined shrimp pond on Hainan, China. (5th May 2023) - Rixen, Tim; Drews, Marco; van Asperen, Hella; Daoru, Wang; Klemme, Alexandra; Warneke, Thorsten
Abstract: Greenhouse gas (GHG) emissions caused by food production contributed on average 23% (12 ± 2.9 P(=10 15 )gCO2 e yr −1 ) to the total anthropogenic GHG emissions between 2007 and 2017. Globally, China has the largest aquatic food production and the South American white shrimp Litopenaeus vannamei ( L. vannamei ) is gaining more and more economic importance. Here, we set-up an GHG monitoring system within a plastic-lined L. vannamei pond on the Chinese island of Hainan and developed a simple box model to better understand processes controlling the aquatic GHG production and emission within and from the pond. Measured data in line with model results showed that an increase of the pond water pH due to liming could have turned the studied pond from a CO2 source into a CO2 sink. Nevertheless, it remained elusive whether liming would finally act as a net CO2 sink to the atmosphere, considering CO2 emissions associated with its supply and the treatment of alkaline pond waters. The transformation of mangroves into aquacultures can, in turn, be seen as a CO2 source for the atmosphere, which enhances the residence of CO2 in the climate system by reducing its burial in sediments. However, in comparison to shrimp cultures in estuaries as well as mangroves and mangroves converted into paddy fields, crab ponds as well as earthen shrimp ponds, methane (CH4 ) and nitrous oxide (N2 O) emission were low in the pond we studied. While N2 O emissions from ponds were in general low, CH4 emission in the studied pond was up to orders of magnitude lower than at the other sites. Shielding pond-waters from impacts of ambient environments such as mangrove soils and ocean waters could be one reason for the low CH4 and N2 O emission. However, the still poorly understood processes controlling fluxes of N2 O and CH4 in aquacultures and mangroves impede the discussion on impacts of aquacultures on the greenhouse effect and hampers the development of further, more specific strategies to lower GHG emissions from shrimp cultures. Highlights: In comparison to other shrimp cultures, methane (CH4 ) and nitrous oxide (N2 O) emission were low in the pond we studied. Shielding pond-waters from impacts of ambient environments such as mangrove soils and ocean waters could be one reason for the low CH4 and N2 O emission. However, processes controlling fluxes of N2 O and CH4 in aquacultures are still poorly understood.